Sobór Watykański II. Tradycja i nowoczesność - BUTTIGLIONE, Rocco; MIKULSKA, Patrycja (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2012)
The author emphasizes that the correct interpretation of the Second Vatican Council, crucial to our perception of the present challenges for the Church, depends on the understanding of the Council’s pastoral character and of the relationship between the Church and the contemporary world. The author discusses two extreme positions concerning the Church’s attitude to the world: that of hostility and that of unconditional acceptance. The proponents of the former would point to the necessity of defending the Church against the world, while the proponents of the latter would encourage the Church to unconditionally accept the world and adapt to it by changing not only the ways of proclaiming the faith to contemporary man, but also the faith itself. The author rejects both positions, showing that the pastoral task of the Council was to identify new ways to proclaim the unchanged faith of the Church to man living in the changed – and continually changing – world. The author believes that to understand the present situation of Christianity – or even the situation of the religious phenomenon as such – it is necessary to find an appropriate philosophical framework for its interpretation. He claims that the widespread ideas of Spinoza and Marx have been proved inadequate in the course of history and that the appropriate conceptual tools may be provided by the thinkers following the tradition beginning with Pascal, such as John H. Newman and Antonio Rosmini. Summarized by Patrycja Mikulska